2016
DOI: 10.17957/ijab/15.0132
|View full text |Cite
|
Sign up to set email alerts
|

Retrotransposon Marker Systems as a Tool to Analyze Molecular Diversity of Mediterranean Pistacia Species

Abstract: Retrotransposon movements could lead to major genome rearrangements because of their special transposition mechanism and may be used to analyze differences between species as a marker system. In this context inter primer binding site (iPBS), inter-retrotransposon amplified polymorphism (IRAP) and retrotransposon-microsatellite amplified polymorphism (REMAP) marker systems were used to resolve genetic differences in 7 Mediterranean Pistacia species (P. vera L. cv. Siirt, P. khinjuk Stocks, P. mutica Fischer, P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Shahi-Gharahlar et al (2011) reported that wild and cultivated genotypes are rich resources of genes for breeding programs. The results are in agreement with the reports published earlier (Ghaemmaghami et al 2013;Kırdök & Çiftçi 2016). According to Xie et al (2010), high, medium, and low loci polymorphism is appointed as PIC > 0.5; 0.5 > PIC > 0.25; and PIC < 0.25, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Shahi-Gharahlar et al (2011) reported that wild and cultivated genotypes are rich resources of genes for breeding programs. The results are in agreement with the reports published earlier (Ghaemmaghami et al 2013;Kırdök & Çiftçi 2016). According to Xie et al (2010), high, medium, and low loci polymorphism is appointed as PIC > 0.5; 0.5 > PIC > 0.25; and PIC < 0.25, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The results of Kılınç et al (2014) and Koç et al (2014) on P. lentiscus based on IRAP and AFLP techniques were supported with the findings of amplification data obtained in our present study in relation to the LTR2 region. Kırdök & Çiftçi (2016) used iPBS, REMAP and IRAP techniques of retrotransposon markers for genetic diversity analysis of Pistacia genus. They found high genetic similarity between P. vera -P. khinjuk, P. atlantica -P. mutica and P. terebinthus -P. palaestina and it was reported that the IRAP technique of retrotransposon-based DNA markers for 7 Mediterranean Pistacia species (total 35 samples) could be used in molecular characterization and molecular breeding trials (Kırdök & Çiftçi 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Kırdök & Çiftçi (2016) used iPBS, REMAP and IRAP techniques of retrotransposon markers for genetic diversity analysis of Pistacia genus. They found high genetic similarity between P. vera -P. khinjuk, P. atlantica -P. mutica and P. terebinthus -P. palaestina and it was reported that the IRAP technique of retrotransposon-based DNA markers for 7 Mediterranean Pistacia species (total 35 samples) could be used in molecular characterization and molecular breeding trials (Kırdök & Çiftçi 2016). In addition, retrotransposon marker systems have also been used in taxonomic studies of the Persian species of the genus Pistacia (P. vera, P. khinjuk, P. atlantica) (Ghaemmaghami et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, no study has been done on P. vera to select salinity tolerant trait using FMs. Molecular marker studies on pistachio are often focused on genetic relationships and diversity, as well as sex determination by using different markers such as Simple Sequence Repeat (SSR) 19 21 , Amplified Fragment Length Polymorphism (AFLP) 22 , 23 , Inter-Simple Sequence Repeats (ISSR) 24 – 27 , Randomly Amplified Polymorphic DNA (RAPD) 28 – 30 , Retrotransposon Microsatellite Amplified Polymorphism (REMAP) 31 , Selective Amplification of Microsatellite Polymorphic Loci (SAMPL) 32 and Single Nucleotide Polymorphism (SNP) 33 .…”
Section: Introductionmentioning
confidence: 99%